STUDYING MARKET CONJUNCTURE AS A FACTOR OF SUCCESSFUL BUSINESS DEVELOPMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article discusses the core concepts of microeconomics—demand and supply—and their interaction, which determines market prices and the quantities of goods and services. Special attention is given to the laws of demand and supply, which explain how changes in the price of a good or service affect the quantity supplied and demanded in the market. The article also analyzes factors influencing these phenomena, such as consumer preferences, income changes, production technologies, and others.